Intralaminar damage in polymer composites in the presence of finite fiber rotation: Part I – Constitutive model. (1st September 2016) - Eskandari, Sina; Andrade Pires, F.M.; Camanho, P.P.; Marques, A.T.
Abstract: The nonlinear behavior of fiber-reinforced composite materials is investigated in the presence of both damage evolution and fiber rotation. While damage mechanisms usually decrease the stiffness of the material and cause premature failure, fiber rotation can lead to a stiffening of the material, due to the reorientation of the fiber towards the loading direction, and delay failure. In this paper, fiber rotation is modeled by an analytical solution and incorporated in Maimi damage model. The predictions of the model with and without fiber rotation are analyzed and compared with the experimental results of IM7/8552 carbon–epoxy composite. The results show the importance of including fiber rotation in the constitutive equations and the accuracy of the overall model in predicting final failure of the specimens.